2017
DOI: 10.1177/1687814017700063
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the tire wear quantity and differences based on vehicle and road coupling method

Abstract: Tire wear quantity and difference is one of the main points that affect the intension of tire road print feature and is under a tight link not only with tire road friction energy but also with vehicle dynamics. The proposed methodology aims to provide a mathematical method to analyze tire marks' feature for prediction the vehicle operating status in pro-and post-crash phases. The kinetic sliding friction coefficient considering the road effect is simplified with the new real contact area model. After, a simpli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 15 publications
0
6
0
Order By: Relevance
“…Ho ¨pping et al 124 Tire simulator The wear of tires increases by appearance of wheels sliding during the braking process. Ma et al 117 Road tests In the case of accidental situation, which is characterized by emergency braking or change of the direction, the wear of tires increases. Kwak et al 122 Road tests and laboratory testing on a real vehicle During the vehicle driving in the curve, the wear of tires increases.…”
Section: Research Methods Conclusionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ho ¨pping et al 124 Tire simulator The wear of tires increases by appearance of wheels sliding during the braking process. Ma et al 117 Road tests In the case of accidental situation, which is characterized by emergency braking or change of the direction, the wear of tires increases. Kwak et al 122 Road tests and laboratory testing on a real vehicle During the vehicle driving in the curve, the wear of tires increases.…”
Section: Research Methods Conclusionmentioning
confidence: 99%
“…70 The same conclusions were also drawn by Li et al, 97 Du et al, 115 Kim and Lee, 89 Li et al, 98 and Cunha et al, 116 that is with the speed increment, the wear of tires rises, which is shown in Table 4. In the research conducted by Ma et al, 117 the authors determined that the greater wear of tires appears on the front axle in respect to the rear one. During the vehicle start, without sliding, the particles concentration was not measurable, while in the case of the racing start (start with wheels sliding), the particles emission from the wear of tires showed signification growth, 118 so and during the vehicle exploitation, in the case of wheels sliding this will cause the increased wear of tires.…”
Section: Influential Factors On the Wear Of Tiresmentioning
confidence: 99%
“…In contrast, the equivalent elastic strain reaches to a greater value on a dry road for both cases. In general, it is understood that the dry road surface would generate more friction than the wet road surface and hence tire wear will be greater on a dry road [18]. Farroni et al [19] had also expressed that a dry road would results in a difficulty for the tire rubber to slip over the road surface which in turns leads to heat build-up in the tire.…”
Section: Analysis Of Steady State Rollingmentioning
confidence: 99%
“…Tire pressure, like other parameters, is a parameter that directly affects tire wear. Tire pressure varies depending on the load in-vehicle use and it is recommended to check frequently [2][3][4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%